Electrocorticography-Guided Resection Enhances Postoperative Seizure Freedom in Low-Grade Tumor-Associated Epilepsy: A Systematic Review and Meta-Analysis. Issue 1 (3rd January 2023) - Warsi, Nebras M.; Mohammad, Amro H.; Zhang, Frederick; Wong, Simeon M.; Yan, Han; Mansouri, Alireza; Ibrahim, George M.
Abstract : BACKGROUND: Low-grade cerebral neoplasms are commonly associated with medically intractable epilepsy. Despite increasing evidence that epileptogenic brain regions commonly extend beyond visible tumor margins, the utility of extended surgical resections leveraging intraoperative electrocorticography (ECoG) remains unclear. OBJECTIVE: To determine whether ECoG-guided surgery is associated with improved postoperative seizure control. METHODS: We performed a systematic review and meta-analysis encompassing both adult and pediatric populations. The primary outcome measure was postoperative seizure freedom as defined by Engel class I outcome. Class I/II outcome served as a secondary measure. Relevant clinical and operative data were recorded. A random-effects meta-analysis based on the pooled odds ratio (OR) of seizure freedom was performed on studies that reported comparative data between ECoG-guided surgery and lesionectomy. RESULTS: A total of 31 studies encompassing 1115 patients with medically refractory epilepsy met inclusion criteria. Seven studies reported comparative data between ECoG-guided surgery and lesionectomy for meta-analysis. Tumor resection guided by ECoG was associated with significantly greater postoperative seizure freedom (OR 3.95, 95% CI 2.32-6.72, P < .0001) and class I/II outcome (OR 5.10, 95% CI 1.97-13.18, P = .0008) compared with lesionectomy. Postoperative adverse events were rare in both groups. CONCLUSION: These findings provide support for the utilization of ECoG-guided surgery to improve postoperative seizure freedom in cases of refractory epilepsy associated with low-grade neoplasms. However, this effect may be attenuated in the presence of concomitant cortical dysplasia, highlighting a need for improved presurgical and intraoperative monitoring for these most challenging cases of localization-related epilepsy.